2012
DOI: 10.4314/ijbcs.v6i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage on the testes of adult rats by sodium metabisulfite (MBS)

Abstract: The effect of sodium metabisulfite (MBS, Na 2 S 2 O 5 ) on the level of malondialdehyde (MDA), testes weight and the activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) as well as the level of glutathione (GSH) were investigated in the testes of Wistar albino rats. The study was performed to elucidate the effect of MBS (520 mg/kg/day) ingestion on lipid peroxidation and the antioxidant enzymes activities. The results showed that MDA level as well as the activity of SOD was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…The free radicals generated can damage nucleic acids and induce mutation according to Meng, (2003) and Meng and Bai, (2004). These results agreed with Mohamad (2011) and Adebayo, and ADenuga (2012). The brain showed tygrolysis and severe degree of encephalomalacia.…”
Section: Discussionsupporting
confidence: 91%
“…The free radicals generated can damage nucleic acids and induce mutation according to Meng, (2003) and Meng and Bai, (2004). These results agreed with Mohamad (2011) and Adebayo, and ADenuga (2012). The brain showed tygrolysis and severe degree of encephalomalacia.…”
Section: Discussionsupporting
confidence: 91%
“…It is estimated that daily sulfite intake from foods and beverages is 180–200 mg/Kg body weight, which is not in agreement with acceptable daily intake level of 0.7 mg/kg body weight ( 11 ). Several studies have shown that ingestion of SMB at a dose of 520mg/kg/day induced oxidative damage in the rats’ testes, liver, and kidney ( 1 , 12 ). The doses of 10,100, and 260 mg/kg/day sulfite were selected from previous studies ( 6 , 13), designed to represent human exposure to different levels of sulfite, which occurred through the consumption of certain foods and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfite salts and sulphur dioxide are added as preservatives to a variety of foods, such as biscuits, chocolate, jam, and in many alcoholic beverages such as beer, wine, etc. and in medications such as parenteral amino acid solutions ( 1 ). Endogenous sulfites are generated in vivo by the catabolism of sulfur-containing amino acids, cysteine and methionine ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations